Family History of Handedness and Language Problems in Mexican Reading-Disabled Children - E. Matute; S. Guajardo-Cárdenas; M.-de-L. Ramírez-Dueñas (Behavioural Neurology)
A sample of 120 Spanish-speaking children, 60 with reading disabilities and 60 normal readers was studied. Individual and family history of handedness, language problems, and reading disabilities were analyzed in each case. The results suggest that reading disabilities are more common among boys, that associated language problems are frequent and that handedness is not a significant factor. Insofar as family history is concerned, there were more affected families and relatives in the reading disabled group than in the control group. Finally an association was established between the variables of handedness and language problems.